Gender, households, and decision‐making for wildfire safety. Issue 4 (13th March 2018) - Tyler, Meagan; Fairbrother, Peter
Abstract : This paper considers the impact of gendered norms on decision‐making for wildfire preparation and response at the household level. Focusing on Australia, it provides a theoretical thematic analysis of data acquired in 107 interviews with residents of nine different localities. It builds on existing research on gender and disaster, as well as on decision‐making and wildfires, and analyses the narratives that centre on 'split' households plans (where a male partner plans to stay and a female partner plans to evacuate) and disagreements within heterosexual couples as to an appropriate wildfire safety plan. The study finds that gender inequality and differences in gendered expectations are likely to create difficult conditions for negotiation between members of a heterosexual couple when there is disagreement over a plan and that this may contribute to risky decision‐making practices and outcomes. The paper reiterates, therefore, the importance of taking into account the social construction of gender in wildfire research and policy.